Analisis Penerapan Model Pembelajaran Problem Based Learning Pada Pembelajaran Matematika Kelas VIII Semester Genap - Muna, Arifatul Hilmi Isfil; Darsono, Darsono; Yohanie, Dian Devita (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze the application of the Problem Based Learning (PBL) learning model in mathematics learning in class VIII even semester. The independent learning curriculum approach in Indonesia emphasizes freedom in the learning process, with the hope of producing a generation that is intellectually strong and has the enthusiasm to be a lifelong learner. The research method used was descriptive-action research, which was carried out at SNP Negeri 1 Grogol with three meetings. The research result show that the activities og teachers and students in implementing the PBL model are in accordance with the steps set out. The teacher succeeded in implementing all stages of the PBL model well, while students showed increased activity during the learning process, especially in asking questions and being avtive in group discussions. Thus, it can be concluded that the PBL learning model can be applied optimally in the context of the independent learning curriculum in Indonesia, although there are still several aspects that need to be improved, especially in student evaluation activities